Desenvolvimento de pickles de frango com adição de diferentes antioxidantes e avaliação da qualidade e aceitabilidade dos produtos - Scheeren, Marina Bergoli (2011)
This study aimed to test the use of residual meat attached to bone structure of the chicken as raw material for the preparation of chicken pickles, using low cost and accessible ingredients. In addition, this study aimed to use different types of antioxidants in the preparation of the pickles and to evaluate the sensory acceptance and preference for these products and to estimate their shelf-life. Frozen chicken were used, with an average weight of 2.5 kg, and they were thawed and subsequently boneless to get the boneless structure with attached meat. These structures passed for a treatment with immersion and boiling in a solution of 2% sodium tripolyphosphate to meat could be more easily removed from bones. On the obtained meat, it was added spices, the broth obtained after meat boiling, vinegar and antioxidants. The product that was not the addition of antioxidants was kept as control, whereas treatments 1, 2 and 3 were the products added 0.01% BHT antioxidant, 0.5% potato peel extract and 0.5% yerba mate extract, respectively. Tests were conducted to evaluate the sensory acceptability (flavour, color, aroma and overall appearance of the products) and preference, in addition to microbiological analysis to evaluate the food security of the pickles and even physical-chemical analysis for composition and to evaluate the deterioration, during the 98 days of storage tested. The results indicated that it was possible to use this meat as raw material of chicken pickles and have a good acceptability. Pickles prepared without the addition of antioxidant and natural antioxidant of potato peel extract were more preferred than the other treatments. The average of protein, fat, moisture, ash and calcium, respectively, were 6.82%, 18.66%, 62.38%, 3.66%, 0.3%. The addition of vinegar and citric acid promoted an acid characteristic in all treatments produced, during the whole storage period. This, combined with the fact that the products were stored at a temperature of 5 °C, contributed to a good preservation of the microbiological chicken pickles. It can be observed because there was no significant increase in the counting of analyzed microorganisms (total aerobic mesophiles, yeasts and molds and coliforms at 45 °C). However, due to oxidative reaction, the estimated time of storage, at 5 °C, to pickles without added antioxidants was 28 days, to pickles which have been added BHT antioxidant, 42 days, and for pickles produced with the addition of extracts of natural antioxidants, 56 days.